2020
DOI: 10.15562/ism.v11i3.706
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Bayi Berat Lahir Rendah (BBLR) dengan kejadian hiperbilirubinemia pada neonatus di RSUD Wangaya, Bali, Indonesia

Abstract: Background: Hyperbilirubinemia is one of the clinical phenomena most often found in newborns and occurs in 60% of > 35 weeks neonates and 80% of < 35 weeks neonates.  Hyperbilirubinemia is one of the most common causes of infant death (2012, SDKI).  Prevalence and severity of hyperbilirubinemia are found to be higher in newborns with low birth weight (LBW). This study aims to determine the relationship between LBW and incidence of hyperbilirubinemia in neonates at Wangaya hospital.Methods: This study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
0
6
0
3
Order By: Relevance
“…11 Males neonates were also the most affected by hyperbilirubinemia (53%) in a study conducted by Yasadipura (2020). 12 Most of the neonates with hyperbilirubinemia in this study were born by spontaneous delivery -noninstrumental/caesarian deliveries (50.8%). This was in line with the observations of a 2017 study conducted by Rohani et al comparing the neonates delivered spontaneously (54.3%) and other neonates who had a cesarean section, vacuum, or forceps (45.7%) deliveries.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…11 Males neonates were also the most affected by hyperbilirubinemia (53%) in a study conducted by Yasadipura (2020). 12 Most of the neonates with hyperbilirubinemia in this study were born by spontaneous delivery -noninstrumental/caesarian deliveries (50.8%). This was in line with the observations of a 2017 study conducted by Rohani et al comparing the neonates delivered spontaneously (54.3%) and other neonates who had a cesarean section, vacuum, or forceps (45.7%) deliveries.…”
Section: Discussionmentioning
confidence: 76%
“…Yasadipura et al (2020) also supported this finding, as they discovered a higher prevalence of hyperbilirubinemia in neonates whose mothers had no history of the maternal disease (54%). 12 Table 2 revealed that 33 (55.9%) of the 59 neonates with hyperbilirubinemia had full-term gestational age at Wangaya Hospital in Denpasar. Hyperbilirubinemia was more common in preterm neonates, occurring in 22.7% of full-term neonates and 53% of preterm neonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penyebab lainnya ialah karena terjadinya peningkatan hemolisis pada bayi sehingga terjadi penumpukan bilirubin indirek di dalam darah. 6,7 Faktor prematuritas pada bayi merupakan salah satu penyebab terjadinya hiperbilirubinemia. Organ dalam tubuh bayi masih belum berkembang dan berfungsi dengan baik.…”
Section: Bahasanunclassified
“…Asfiksia dapat menyebabkan asidosis, yaitu pH darah <7, yang dapat menyebabkan gangguan transportasi dan konjugasi bilirubin sehingga terjadi penumpukan bilirubin dan bermanifestasi kuning pada kulit. 11 Penelitian oleh Yasadipura et al 7 melaporkan terdapatnya hubungan antara BBLR dengan kejadian hiperbilirubinemia pada bayi baru lahir di RS Wangaya (p=0,042) dengan rasio prevalensi 2,13 yang menyiratkan bahwa BBLR merupakan faktor risiko kejadian hiperbilirubinemia. Salah satu penyebab kejadian hiperbilirubinemia pada BBLR yaitu imaturitas hati yang berakibat terhambatnya proses konjugasi dari bilirubin indirek ke direk sehingga terjadi ikterus.…”
Section: Bahasanunclassified